A protocol to expand plant nuclei - Kubalová, Ivona; Schmidt Černohorská, Markéta; Huranová, Martina; Weisshart, Klaus; Houben, Andreas; Schubert, Veit (Methods in cell biology, 2021)
The resolution achieved by conventional light microscopy is limited by light diffraction. This obstacle can be overcome either by optical super-resolution techniques or by the recently developed method to physically expand specimens, called expansion microscopy (ExM). The method utilizes polymer chemistry and the ability of a swellable polyelectrolyte hydrogel to absorb water, and thus to expand its size. The procedure was successfully applied to different species and tissue samples, mostly from the animal kingdom. Physically expanded nuclei and chromosomes in combination with specific protein labeling and super-resolution microscopy may provide new insight into the ultrastructure, dynamics, and function of plant chromatin. Here we provide a detailed protocol to expand isolated plant nuclei and visualize proteins by indirect immunolabeling. With the focus on chromatin structure, we expanded isolated barley nuclei from root tips and visualized the centromere-specific histone H3 variant CENH3. The achieved physical expansion of ~4.2 times allowed the detection of DAPI-labeled chromatin structures already by conventional wild-field (WF) microscopy with a maximal resolution of ~50-60nm. By applying structured illumination microscopy (SIM), doubling the WF resolution, chromatin structures at a resolution of ~25-35nm were observed. However, a certain distortion of the centromeric chromatin ultrastructure became obvious.
Keywords: centromera; buněčné jádro; rostliny; Histones; CENH3; Plant chromatin; Structured illumination microscopy; Microscopy; Rabl configuration; histony; Plants; Isolated nuclei; Chromatin; Centromere; Expansion microscopy; mikroskopie; Cell Nucleus; chromatin